Vasilij Vasko Polič, vrhovni sodnik svetnik (1940–2023) - Golob, Peter (Pravnik, 2023)
In the final days of November 2023, we bade farewell to Vasko Polič, a man of diverse talents and remarkable compassion. A distinguished athlete in his youth, Polič’s career spanned a variety of fields: a lawyer, actor, writer, poet, musician, and a veritable encyclopaedia of cinema. However, his most notable role was as the Supreme Court judge, a position he held for 24 years. Elected in 1986, he served until his retirement in 2010. His tenure coincided with pivotal moments in the evolution of Slovenian statehood and its legal system. Given the significance of the role of Supreme Judge, his period in office profoundly influenced the legal system, particularly in the field of administrative law.
Keywords: actor; erotica; erotika; igralci; in memoriam; nekrologi; obituary; pesniki; poet; supreme judge; Vasko Polič; vrhovni sodniki